Glow up: does a professional photoshoot intervention affect self-esteem and emotions among adolescent psychiatric patients?—A longitudinal intervention study - Kornelius Winds; Kornelius Winds; Theresa Marka; Theresa Marka; Bernhard Salcher; Nicole Rieser; Christine Skrivanek; Michelle Hochrainer; Julia Trost-Schrems; Lucas J. Rainer; Lucas J. Rainer; Lucas J. Rainer; et al. (Frontiers in Psychiatry, 2024)
BackgroundToday, online communication is shaped by a billion-dollar social media (SM) and social networking site (SNS) industry. Visual content consumed by children and adolescents has been shown to influence behavioral patterns, state emotions, and self-esteem (SE). In this study, we introduced a novel intervention creating visual content through a professional photoshoot and investigated its impact on state emotions and SE in child and adolescent psychiatric (CAP) patients.MethodsStandardized and validated self-rating questionnaires were used to assess SE, state emotions, coping mechanisms, psychopathological symptoms, and internet use behavior at baseline. SE and state emotions were monitored at different time points around a professional photoshoot within 45 CAP patients (30 female patients; mean age, 15.1 years) using a longitudinal design.ResultsWithin-subject repeated-measures ANOVA and bootstrapped paired-sample t-tests showed a significant fluctuation in state emotions and SE throughout the intervention. Spearman correlations and univariate logistic regressions revealed that internalizing symptomatology and maladaptive coping significantly worsened the outcome of the intervention on state emotions and SE in girls. Internet-related variables heightened the positive effect of the intervention in boys and lowered SE in girls during the intervention.ConclusionThe photo intervention had various gender-specific effects. Boys did benefit from the intervention in terms of longitudinal outcome on positive state emotions (PE) and SE, even positively influenced by SNS and SM. Thus, it might be concluded that online social comparison was processed more beneficial in boys. In contrast, when working with visual content in girls, psychopathology and coping must be considered. Internet consumption in general, especially SM and SNS, was related to low SE in girls. Nevertheless, when therapeutically accompanied, the “glow up moment” during the shoot (high on PE and SE; low on negative state emotions) could be used as an index moment for therapeutic reflection.